WATAK DAN PERJUANGAN PEREMPUAN DALAM NOVEL-NOVEL KARYA PENULIS PEREMPUAN INDONESIA DAN MALAYSIA AWAL ABAD 21 - Widyastuti Purbani (LITERA, 2013)
This study aims to identify and reveal the traits and struggles of female characters in eight novels written by Indonesian and Malaysian women writers in the early 21stcentury. This is a qualitative study employing content analysis. The study reveals that all main female characters in these eight novels are strong and tough women living in a discriminativepatriarchal society in which women are seen as the second class society and object of sexual desire. The main female characters in the both Indonesian and Malaysian novels under study are fighting for either themselves or other female characters against gender discrimination and sexual abuse. Some female characters struggle to gain knowledge and skills for a better position, and some struggle to get economic welfare. While the Indonesian characters use human rights for gender equity and moral justice, the Malaysian characters use religious and moral conduct as the foundation for their struggle.